GAYA BELAJAR MAHASISWA D3 TATA BUSANA FAKULTAS PARIWISATA DAN PERHOTELAN UNIVERSITAS NEGERI PADANG - Siti Mashitah; Ernawati Ernawati (JUPE : Jurnal Pendidikan Mandala, 2022)
Basically, every student has a different learning style. This study aims to determine the dominant learning style in D3 Fashion Design students, Faculty of Tourism and Hospitality, Padang State University, which consists of visual, auditory and kinesthetic learning styles. The research method is descriptive quantitative. The population in this study were D3 Fashion Design students who were registered in the 2019 semester of January-June 2022, class of 2019, 2020 and 2021. The sample technique used was simple random sampling determined by the Slovin formula and obtained as many as 60 students. Data collection using a questionnaire. Analysis of research data using descriptive statistical analysis. The results showed that the learning style of D3 Tourism and Hospitality Fashion Design students at Padang State University with a visual learning style value of 42%, auditory 35% and kinesthetic 23%. Based on the results of data analysis, it can be concluded that the most dominant learning style for D3 Fashion Design students is visual learning style.